Revealing Spiritual-Based Mental Accounting: (Case Study at College X) - Wildan, Wildan Khisbullah Suhma; Sulistiyo, Agung Budi; Prasetyo, Whedy (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
This study aims to find out about the existence of mental accounting and its obstacles in a Faculty (Faculty C) at an Islamic College in the Tapal Kuda area, East Java. This research is quantitative research with lecturers and managers of Faculty C at the university as an informant. Researchers used the interaction analysis method developed in this study. From the results of interviews, observations, and documentation conducted by the author, it was found that in uncovering spiritual-based mental accounting, there are three major underlying points, namely the Value in Nrimo Ing Pandum, the Productivity Development, and Ikhlas Beramal. Nrimo Ing Pandum is God's will to provide an environment and opportunity to work productively and successfully. The productivity of human resources for educators is given responsibility by making textbooks for each subject taught. Ikhlas beramal occurs because of a charitable process that is influenced by a charity that is continuously carried out by individuals.